EFFICACY OF INTERFERENTIAL THERAPY ON SELECTED CARDIOPULMONARY PARAMETERS OF ASTHMATIC PATIENTS WITH POST COVID19 EXPOSURE: A STUDY PROTOCOL OF A RANDOMIZED CONTROL TRIAL (International Journal of Physiotherapy, 2023)
Background: Interferential Therapy (IFT) is the administration of two medium-frequency currents to the skin, stimulating varying systems in the body using specific frequencies and frequency ranges. IFT in the thoracic region aims to reduce muscle soreness in the chest and upper back, reduce muscular fatigue and induce mucus expectoration. This study is designed to test the efficacy of IFT on bronchial asthma patients exposed to the SARS-CoV-2 virus.Methods: IFT will be administered as an intervention to 28 asthma patients with and without a history of COVID-19 exposure for 20 minutes. Six continuous outcome variables at different points will be utilized as an outcome measure; the selected Baseline Pulmonary Function Test (PFT) and Cardiopulmonary Variables (CVS) will be assessed upon entry into the study and after every intervention, while asthma quality of life and asthma control test will be measured fortnightly. In addition, participants will be required to visit the study location 3 times per week for 12 weeks.Results: The means ± SD will be compared, while the participant's outcome variables will be evaluated for study homogeneity at baseline. Repeated measures of MANOVA will be used to evaluate the study outcome within group participants. In contrast, a one-tail independent t-test will be used to evaluate the efficacy of IFT on bronchial asthma patients with Post COVID-19 exposure across groups. The level of significance will be set at P